Succeeding with agile hybrids : project delivery using hybrid methodologies - Belling, Shawn (Apress, 2020)
Successfully delivering projects at an organization can happen with the careful utilization of a variety of methods and practices. The best approach is a hybrid framework that adapts in real time to your team and its needs. This book addresses the practical realities of project delivery in the 21st century. The agile method is well-known and well-covered. Author Shawn Belling dives deeper with his expertise into organizational management and investigates how to best execute a graceful mix of waterfall methods, agile, and phase-based approaches. Each business and goal requires flexibility for a unique journey to success, and Belling provides the practitioner with practical, real-world examples and patterns of these methodologies. Succeeding with Agile Hybrids is the answer to the diversity of needs within your team. Whether you are an aspiring or current project manager, scrum master, or mid-level manager, this book will greatly benefit you and your goals for project delivery. Hybrid agile is the future, and you will be well-equipped to tackle it with Succeeding with Agile Hybrids on your shelf. You will: See how hybrid agile is a common de facto approach to project management Review common, practical and real-world examples and patterns of hybrid agile project management Evaluate projects and organizations for using hybrid agile or agile project management.